Microstructural and paleomagnetic insight into the cooling history of the IAB parent body - Nichols, CIO; Krakow, R; Herrero-Albillos, J; Kronast, F; Northwood-Smith, G; Harrison, RJ (Elsevier, 2018)
The IABs represent one of only two groups of iron meteorites that did not form by fractional crystallization of liquid Fe-Ni in the core of a differentiated planetesimal. Instead, they are believed to originate from a partially differentiated body that was severely disrupted by one or more impacts during its early history. We present a detailed microstructural and paleomagnetic study of the Odessa and Toluca IAB meteorites, with a view to further constraining the complex history of the IAB parent body. X-ray photoemission electron microscopy and energy dispersive spectroscopy were used to generate high-resolution Ni/Fe maps. The crystallographic architecture of Odessa was analysed using electron backscatter diffraction. Paleomagnetic signals and the magnetic properties of several microstructures were also assessed using X-ray magnetic circular dichroism. Odessa exhibits a complex series of microstructures, requiring an unusual evolution during slow cooling. A conventional Widmanstätten microstructure, consisting of multiple generations of kamacite lamellae surrounded by M-shaped diffusion profiles, developed via continuous precipitation to temperatures below ∼400 °C. Multiple generations of pearlitic plessite nucleated from kamacite/taenite (T > 400 °C) and tetrataenite rim/taenite interfaces (T < 400 °C), via a process of discontinuous precipitation. Rounded rafts of Ni-rich taenite, observed within some regions of pearlitic plessite, are shown to have the same crystallographic orientation as the parental taenite, and a non-standard orientation relationship with the enclosing kamacite. Contrary to current theories, these rafts cannot have formed by coarsening of pre-existing pearlitic plessite. A new bowing mechanism is proposed, whereby rafts of Ni-enriched taenite form between advancing lobes of an irregular reaction front during discontinuous precipitation. Subsequent coarsening leads to the growth of the taenite rafts, and the partial or complete removal of pearlite lamellae, resulting in spheroidised plessite with a crystallographic architecture matching the experimental observations. We find no evidence for a strong magnetic field on the IAB parent body, suggesting it did not have an active core dynamo at the time of cloudy zone formation. This supports the prediction that the IAB parent body was unable to form a significant core due to the redistribution of metal during an earlier impact event.